2023
DOI: 10.1039/d2bm01609e
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free and cytokine-free self-assembling peptide hydrogel-polycaprolactone composite scaffolds for segmental bone defects

Abstract: Segmental bone defects over the self-healing threshold are a major challenge for orthopedics. Despite advances in clinical practice, traditional tissue engineering methods are limited by the addition of heterogeneous cells...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(54 reference statements)
1
3
0
Order By: Relevance
“…To examine the microstructure of the hydrogels with varying CNT doping concentrations, electron microscopes were employed. In Figure 1 B, scanning electronic microscopy (SEM) images revealed stacked layers and bulk structures for FEK, consistent with previous reports [ 23 ]. The FEK/C 1 , FEK/C 2 , and FEK/C 3 hydrogels exhibited similar morphologies to FEK under SEM.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To examine the microstructure of the hydrogels with varying CNT doping concentrations, electron microscopes were employed. In Figure 1 B, scanning electronic microscopy (SEM) images revealed stacked layers and bulk structures for FEK, consistent with previous reports [ 23 ]. The FEK/C 1 , FEK/C 2 , and FEK/C 3 hydrogels exhibited similar morphologies to FEK under SEM.…”
Section: Resultssupporting
confidence: 91%
“…Peptide hydrogels, known for their good biocompatibility, provide an extracellular microenvironment (ECM)-like environment that promotes cell attachment and proliferation [ 21 , 22 ]. In previous studies, a non-immunogenetic octapeptide (FEFEFKFK) was designed and synthesized [ 23 , 24 ]. This octapeptide can form self-assembling peptide hydrogel (SAPH) with a typical structure consisting of nano-sized β sheet stacks, also called FEK hydrogels for short.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that PAA-RGD polypeptide hydrogel had suitable biodegradability, excellent biocompatibility, and low immunogenicity, which are beneficial for the proliferation and migration of rabbit bone marrow mesenchymal stem cells and promote the repair of rabbit osteochondral tissue. Zhu et al [ 62 ] promoted the growth, proliferation, and secretion of extracellular matrix and cytokines in bone marrow stem cells by adding a polypeptide hydrogel based on traditional PCL scaffolds to improve the hydrophilicity and biocompatibility, thereby facilitating the repair of bone defects. Yin et al [ 30 ] designed and synthesized a RADA peptide hydrogel with good biocompatibility, which promoted the proliferation of tendon stem cells and inhibited cell aging.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in recent research have demonstrated that liposomes and cyclodextrins can be used for the delivery of CPT to reduce its toxicity and promote its properties. [15][16][17][18][19][20][21][22][23] However, most of these carriers do not meet the requirements of a high drug-delivery efficiency, ease of dispersion, and controlled particle size, which are key to clinical translation. 24,25 Calixarene (CA), a crucial component of supramolecular families, is a supramolecular macrocyclic compound made of phenol units connected by methylene bridges, with an easy chemical modification of the upper and lower edges of the phenol units, an adjustable size, and conformation of the hydrophobic cavities in the structure.…”
Section: Introductionmentioning
confidence: 99%